Prevalence and association of renal disorders in Saudi adult patients with psoriasis and psoriatic arthritis: a tertiary-center retrospective cross-sectional study - Mishari Alrubaiaan; Abdullah Alhobabi; Raghad Alharthi; Saad Alsulaiman; Abdullah Altasan; Ibrahim Momen; Mohammad Almohideb (Dermatology Reports)
Psoriasis, a chronic inflammatory skin disease, is connected to psoriatic arthritis, a chronic inflammatory arthritis. Recent studies have also linked psoriasis and psoriatic arthritis to various renal disorders. This research aims to determine the prevalence and association of renal disorders in adult patients with psoriasis and compare those findings with adult patients with psoriatic arthritis. This retrospective cross-sectional study included 485 participants with psoriasis. The study evaluated demographics, psoriasis type, the presence of psoriatic arthritis, and related comorbidities, excluding individuals under the age of 18 or those with no verified diagnosis. Medical records were reviewed for renal problems, and a multivariate logistic regression was used to investigate the relationship between psoriasis and psoriatic arthritis. Overall, 10.1% of psoriatic individuals had psoriatic arthritis. The mean age at diagnosis was 41.59±15.58 years, with 54.2% female. Plaque psoriasis was identified in 87.2% of patients, with 46% classified as obese (BMI≥30). Chronic renal failure was seen in 6.2% of psoriasis patients, and 6.1% of psoriatic arthritis patients. In our study, chronic renal failure rates were similar in psoriasis and psoriatic arthritis. Psoriatic arthritis was associated with an increased risk of acute kidney damage, transplantation, and dialysis.